Assessing the Scientific Literacy of Prospective Biology Teachers - Baiq Fatmawati; Husnul Khotimah (Jurnal Penelitian Pendidikan IPA, 2023)
Scientific literacy is one of the goals of science education so that students can use scientific principles to address science-related problems. A person who possesses scientific literacy was able to recognize, analyze, and design scientific research as well as interpret data using scientific evidence. Students that are scientifically literate can approach challenges by using a scientific approach. Nevertheless, not all of these skills are possessed by students, particularly those who are freshmen in college. The purpose of this study was to determine the scientific literacy skills of prospective biology teachers using the scientific method in the learning process. This research is pre-experimental with the one group pretest – posttest design, respondents was 31 new student of biology education in first semester. Worksheets based on the scientific method are used in the research instrument. Data analysis using the SPSS 25.0 program, paired t test statistical analysis was used for data analysis. The research findings can be concluded that met a significance threshold of 0.000 (p value 0.05), indicating that there was a difference between the typical student scores before and after the scientific method was used